PENGARUH BUDAYA TRI HITA KARANA PADA HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY DAN NILAI PERUSAHAAN PADA INDONESIA TOURISM DEVELOPMENT CORPORATION - I Gusti Ayu Agung Omika Dewi; Ni Komang Biyantari (Jurnal Ilmiah Akuntansi & Bisnis, 2017)
The Influence of the Culture of Tri Hita Karana on the Relationship Between Corporate Social Responsibility and Firm Value at Indonesia Tourism Development Corporation. The purpose of this study was 1. To determine the influence of Corporate Social Responsibility to Corporate Values Indonesia Tourism Development Corporation (ITDC) , 2. To know that the implementation of Tri Hita Karana Cultural influence on relations between Corporate Social Responsibility to Corporate Values   Indonesia Tourism Development Corporation ( ITDC ). In this study the authors used the GRI (Global Reporting Intiative) Generation 4 with 91 items of disclosure to assess the company's Corporate Social Responsibility . Variable Value Companies are judged on analysis Tobins'Q. Variable Tri Hita Karana is measured by using a check list contained in THK Awards Handbook, published by the Provincial Government of Bali . Data analysis techniques in this research is the analysis of MRA ( Moderated Regression Analysis ) or interaction test.The results found that 1 ) Corporate social responsibility ( CSR ) affects the value of the company Indonesia Tourism Development Corporation . 2 ) Cultural Tri Hita Karana effect on relations corporate social responsibility and the value of the Indonesia Tourism Development Corporation.Keywords: Corporate Social Responsibility, Corporate Values, Tri Hita Karana